KOLABORASI PENDIDIKAN VOKASI DENGAN TEKNOLOGI AI: TREN TEKNOLOGI AI UNTUK MENINGKATKAN KOMPETENSI SISWA SMK 2 KLATEN - Wuryandari, Aryati; Prasetyo, Hendro Joko; Muryanto (LPPM Universitas Widya Dharma Klaten, 2025)
The technological transformation of the Industrial Revolution 4.0 era and the shift towards Society 5.0 have fundamentally changed the social, economic, and educational landscape. Vocational High Schools (SMK), as the vanguard of vocational education, play a strategic role in producing skilled workers who are ready to face the challenges of technology-based industries, particularly those related to artificial intelligence (AI). However, there is a gap between industry needs and the competencies of students and teachers at vocational schools. To address this, the Diploma 3 Vocational Study Program in Informatics Management at Widya Dharma University, Klaten (Unwidha) conducted an introductory training on AI technology for students of SMK Negeri 2 Klaten. This activity aims to improve technological literacy and student readiness for the increasingly AI-dominated workforce. The implementation method included lectures, discussions, and practical training, with a focus on introducing basic AI concepts and their practical applications. The results of the activity showed an increase in students' understanding and skills in AI technology, as well as strengthening collaboration between higher education and vocational education. It is hoped that this activity can be continued and integrated into the vocational education curriculum to increase the relevance of learning to industry needs. Keywords : Vocational High Schools, AI skills, AI technology, vocational education